Psychology of Sian Soor Tennis Junior Athletes in Competition - Ince Abdul Muhaemin M; Marsuki; Andi Syaiful; Ipa Sari Kardi; Ibrahim (Indonesian Journal of Physical Education and Sport Science)
Studi purpose: As an athlete who has a demand to excel when competing, anxiety in athletes becomes one of the conditions that athletes often experience which affects the athlete's performance in facing the match. One of the mental factors that trigger athletes' psychology is anxiety, self-confidence, and resilience factors. This study aimed to determine the level of anxiety, self-confidence, and resilience of Sian Soor junior athletes in the sport of tennis.